The Life and Letters of Herbert Spencer - Duncan, David 1839-1923 (Cambridge library collection. Philosophy, 1908)
One of the most famous intellectuals of the second half of the nineteenth century, Herbert Spencer (1820–1903) wrote across an impressive range of scientific and philosophical subjects. Although at the time his work was successful and influential, especially in America, it has since been subjected to criticism and reassessment. Principally remembered for his evolutionary theory and for coining the term 'survival of the fittest', Spencer came to be regarded as a Social Darwinist and proponent of unrestricted capitalism. In the field of sociology, he advocated the application of scientific examination to social phenomena, and his individualist philosophy provided inspiration for later libertarian thinkers. Published in 1908 by David Duncan (1839–1923), this substantial biography closely tracks Spencer's developing interests, closing with an assessment of his character and significance. It contains an abundance of extracts from letters to such figures as Charles Darwin, John Stuart Mill and T. H. Huxley